Favorable Preclinical Pharmacological Profile of a Novel Antimalarial Pyrrolizidinylmethyl Derivative of 4-amino-7-chloroquinoline with Potent In Vitro and In Vivo Activities - Basilico, Nicoletta; Parapini, Silvia; D’Alessandro, Sarah; Misiano, Paola; Romeo, Sergio; Dondio, Giulio; Yardley, Vanessa; Vivas, Livia; Nasser, Shereen; Rénia, Laurent; Russell, Bruce M.; Suwanarusk, Rossarin; et al. (Biomolecules, 2023)
The 4-aminoquinoline drugs, such as chloroquine (CQ), amodiaquine or piperaquine, are still commonly used for malaria treatment, either alone (CQ) or in combination with artemisinin derivatives. We previously described the excellent in vitro activity of a novel pyrrolizidinylmethyl derivative of 4-amino-7-chloroquinoline, named MG3, against P. falciparum drug-resistant parasites. Here, we report the optimized and safer synthesis of MG3, now suitable for a scale-up, and its additional in vitro and in vivo characterization. MG3 is active against a panel of P. vivax and P. falciparum field isolates, either alone or in combination with artemisinin derivatives. In vivo MG3 is orally active in the P. berghei, P. chabaudi, and P. yoelii models of rodent malaria with efficacy comparable, or better, than that of CQ and of other quinolines under development. The in vivo and in vitro ADME-Tox studies indicate that MG3 possesses a very good pre-clinical developability profile associated with an excellent oral bioavailability, and low toxicity in non-formal preclinical studies on rats, dogs, and non-human primates (NHP). In conclusion, the pharmacological profile of MG3 is in line with those obtained with CQ or the other quinolines in use and seems to possess all the requirements for a developmental candidate.